THE GHOSTS OF PORTALES: BANDITRY AND JuDICIAL PRACTICES IN CHILE, 1830-1850 - Palma Alvarado, Daniel (Revista de Historia Social y de las Mentalidades, 2012)
Focusing on the life-trajectory of an  individual bandit in Chile’s central  zone, and on his experiences dealing  with justice and punishment, the article  traces the constitution of the so-called  “Portalean Order” in the field of criminal  justice. It is especially concerned with  the exchanges between the State and the  bandits in a context where the strains between  the government’s disciplinary goals and the  resistance of those who were subjected to  greater vigilance and punishment became  particularly visible.
Keywords: banditry; justice; crime; popular classes; portalian order